Reconstruction of the Integration of the Powers of the Religious Courts and the Population Registry Office in Updating Civil Status Following Divorce - Rohmad Bahrudin; Fadil Fadil; Isroqunnajah Isroqunnajah (Jurnal Multidisiplin Sahombu, 2026)
A legally binding marriage decree should directly change the legal status of the parties, including their marital status in population administration. However, such changes still depend on public reporting to the Population and Civil Registration Office, leading to fragmentation of authority between the judicial system and population administration. This study aims to analyze the authority gap between the Religious Court and the Population and Civil Registration Office in updating post-divorce population status and to reconstruct a digital government-based authority integration model. The study uses a normative-empirical legal method (socio-legal research) with guidelines from regulations, conceptualizations, and cases. Data were obtained through document analysis studies, laws and regulations, and semi-structured interviews at the Malang Regency Religious Court and the Malang Regency Population and Civil Registration Office, then analyzed qualitatively using deductive-critical reasoning. The results of the study indicate the absence of a data interoperability mechanism that connects legally binding divorce settlements with the Population Administration Information System (SIAK), resulting in dualism of legal status between judicial and administrative status. The implementation of e-Court and Electronic Divorce Certificates has only resulted in the digitization of documents and internal judicial administrative processes without realizing cross-sector integration. The novelty of this research is the Trigger-Based Administration Integration Model, which positions a legally binding divorce decree as an automatic trigger for updating residency status through the interoperability of Application Programming Interface (API)-based information systems between the Supreme Court and the Directorate General of Population and Civil Registration, thereby strengthening legal certainty, population data accuracy, and the effectiveness of national digital governance.